2021
DOI: 10.26905/jp.v18i2.7056
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of “Kampus Mengajar”: an effort to increase participation at the University of Merdeka Malang

Abstract: “Kampus Mengajar” aimed to assist the process of teaching and learning at the elementary-junior high school level through technology adaptation, teaching numeracy and literacy, and administrative procedures. The deployment of students during the COVID-19 pandemic, which required learning to be conducted online, will significantly help the school, especially related to technology adaptation. However, this program was less attractive to students and lecturers at the University of Merdeka Malang; this was evident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
(4 reference statements)
0
2
0
3
Order By: Relevance
“…After reviewing nearly all existing literature on Kampus Mengajar, the researchers found that most of the published literature focused primarily on how the program is run on Java Island. The most predominant province in reporting the impact of their program is East Java (Anwar, 2021;Ashari et al, 2022;Bali et al, 2022;Rachman et al, 2021;Rosita & Damayanti, 2021;Salsabila et al, 2022;Setyadi et al, 2021;Tsamroh et al, 2021), closely followed by West Java (Khairunnisa & Kurniawan, 2021;Mulyati et al, 2021;Safaringga et al, 2022;Usral et al, 2022;Utami, 2021). Research also covers the program in Central Java (Prasandha & Utomo, 2022;Pristya et al, 2022;Santoso et al, 2022;Widiyono et al, 2021;Widjanarko et al, 2021), Jakarta (Anugrah, 2021;Fatonah et al, 2021;Lestari et al, 2023;Rahmadani et al, 2022), Bengkulu (Nurhasanah & Nopianti, 2021), West Nusa Tenggara (Hikmawati et al, 2022), West Sumatra (Rahim & Suryani, 2022), North Sumatra (Martina et al, 2022) and South Sumatra (Hendrowati & Sunanto, 2021;Khotimah et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…After reviewing nearly all existing literature on Kampus Mengajar, the researchers found that most of the published literature focused primarily on how the program is run on Java Island. The most predominant province in reporting the impact of their program is East Java (Anwar, 2021;Ashari et al, 2022;Bali et al, 2022;Rachman et al, 2021;Rosita & Damayanti, 2021;Salsabila et al, 2022;Setyadi et al, 2021;Tsamroh et al, 2021), closely followed by West Java (Khairunnisa & Kurniawan, 2021;Mulyati et al, 2021;Safaringga et al, 2022;Usral et al, 2022;Utami, 2021). Research also covers the program in Central Java (Prasandha & Utomo, 2022;Pristya et al, 2022;Santoso et al, 2022;Widiyono et al, 2021;Widjanarko et al, 2021), Jakarta (Anugrah, 2021;Fatonah et al, 2021;Lestari et al, 2023;Rahmadani et al, 2022), Bengkulu (Nurhasanah & Nopianti, 2021), West Nusa Tenggara (Hikmawati et al, 2022), West Sumatra (Rahim & Suryani, 2022), North Sumatra (Martina et al, 2022) and South Sumatra (Hendrowati & Sunanto, 2021;Khotimah et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Program tersebut sesuai dengan Permendikbud Nomor 3 Tahun 2020 yang merupakan regulasi hukum dalam meningkatkan mutu pembelajaran dan lulusan perguruan tinggi (Jenderal & Tinggi, n.d., 2023). Merdeka belajar ini mendorong guru dan siswa untuk secara leluasa mengembangkan pengetahuan, keterampilan, sikap yang dimiliki (Meilia & Erlangga, 2022;Tsamroh et al, 2021). Tuntutan ini akan mendorong siswa untuk mengembangkan keterampilan beradaptasi dengan lingkungan sesuai dengan kebutuhan abad 21.…”
Section: Pendahuluanunclassified
“…Berbagai penelitian telah dilakukan terkait dengan kampus mengajar (Fauzi et al, 2021;Hamzah, 2021;Syamsuddin et al, 2021;Tsamroh et al, 2021). Penelitian yang dilakukan oleh Tsamroh et al (2021), memberikan dampak analisis kampus mengajar terhadap kebijakan di Universitas Merdeka Malang.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Studies that discuss MBKM have been widely published in journal and papers in proceedings, such as studies on the concept of independent learning (5); ((6); ((7), (8), (9). (10) (11).…”
Section: Introductionmentioning
confidence: 99%